The Effect of Asset Procurement Planning, Regulation, Asset Inventory, Information Systems and Human Resources Competence on Fixed Assets Optimization - Naomi Naomi; P. Basuki Hadiprajitno (Journal of Business Social and Technology, 2023)
This study examines the influence of asset procurement planning, regulations, asset inventory, information systems and human resource competence on the optimization of fixed assets (studies on asset administration at the Financial Services Authority). The research population is the employees of the Financial Services Authority. Determining the number of samples can be done by means of statistical calculations, namely by using the Slovin formula. This formula is used to determine the sample size of a known population, namely 3,134 Financial Services Authority employees. Furthermore, to perform data analysis, multiple linear regression through the use of SPSS software as a tool is used in this study. The results showed that (H1) was accepted with a significance value of 0.000 which is less than 0.050, needs planning and asset valuation had a positive and significant effect on asset optimization. (H2) is accepted with a significance value of 0.024 which is less than 0.050. An important aspect of asset optimization is the regulatory aspect. (H3) is accepted with a significance value of 0.000, which is less than 0.050. Asset inventory and legal audit have a positive and significant impact on the optimization of fixed assets. (H4) is accepted with a significance value of 0.000 which is less than 0.050, the management information system assists the process of managing finances and assets and reduces the risk of fraud from certain individuals. (H5) is accepted with a significance value of 0.003 which is less than 0.050, fixed asset management is weak human resource competence and lack of responsibility from related parties in managing fixed assets. So that competent human resources are needed in asset management